Real‐Time Controls of Designer Surface Plasmon Polaritons Using Programmable Plasmonic Metamaterial. Issue 1 (7th November 2016) - Zhang, Hao Chi; Cui, Tie Jun; Xu, Jie; Tang, Wenxuan; Liu, Jun Feng
Abstract : Manipulating the dispersion behaviors of electromagnetic (EM) waves at subwavelength scale provides many exciting physical phenomena and functionalities such as the phase matching, gain enhancement, super resolution, and slow light. Among the dispersion manipulations, surface plasmon polaritons (SPPs) are typical EM modes to control the wave flows owing to their sensitivity to the designed decorations on the metal–dielectric interfaces. However, either on metal–dielectric interfaces or decoration surfaces, it is challenging to construct reconfigurable and programmable SPPs to control SPP waves dynamically in real time. Here, the authors propose the concepts of coding and programmable designer SPPs, which are realized by an ultrathin corrugated metallic strip loaded with active devices and a digital system. Based on the big freedom provided by the coding representation, the authors experimentally demonstrate that a simple programmable SPP system can reach at least three different digital‐analog functionalities: (1) SPP logical gate based on 1‐bit coding; (2) SPP digital phase shifter based on 2‐bit coding; and (3) controllable SPP slow waves based on 4‐bit coding. Such functionalities can be switched in real time using a single prototype and the digital control system. Abstract : The concept of programmable designer surface plasmon polaritons (SPPs) is first explored. And a new kind of planar SPP waveguide with dynamically‐controllable functionalities is also proposed to achieve three digital‐analog functionalities as examples: (1) designer SPP logic gate based on 1‐bit coding SPPs, (2) SPP digital phase shifter based on 2‐bit coding SPPs, and (3) controllable slow‐wave generations based on 4‐bit coding SPPs.